Pengaruh Pemberian Jus Wortel Terhadap Penurunan Tekanan Darah Pada Ibu Hamil - Mappiati, Misrawati; Marliah, Marliah; Dawa, Oklin (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
Carrots contain antioxidant catheronoids which can neutralize free radicals so that hypertension can be prevented. The aim of this research is to determine the effect before and after administering carrot juice on reducing blood pressure in pregnant women whose gestational age is over 20 weeks at the Jumpandang Baru Community Health Center. This research uses Pre-Experimental with the One Group Pretest-Posttest method. The sampling technique uses purposive sampling. There were 30 samples of respondents in this study, all of whom were treated with carrot juice to pregnant women. The results of research using the T pairedet test where the value ρ = .000 < α = 0.05, there is an effect of giving carrot juice on reducing blood pressure in pregnant women at the Jumpandang Baru Community Health Center in 2024. The conclusion is that there is an effect of giving carrot juice on reducing blood pressure in pregnant women at the Jumpandang Baru Community Health Center in 2024.